2004
DOI: 10.1210/jc.2003-031626
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Insulin Resistance in Patients with Idiopathic Hirsutism

Abstract: 2 ) were included in the study. Eight of 32 patients with IH had BMI higher than 30 kg/m 2 . The presence of insulin resistance was investigated by using basal insulin levels, the oral glucose tolerance test, the iv insulin tolerance test, and the homeostasis model assessment (HOMA) score in both groups. Six (18.7%) patients had impaired glucose tolerance (IGT). Overall, patients with IH had significantly (P < 0.05) higher basal insulin levels (10.5 ؎ 1.1 mU/liter vs. 5.7 ؎ 0.9 mU/liter) and HOMA scores (2.0 ؎… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
49
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 26 publications
5
49
1
1
Order By: Relevance
“…Unluhizarci et al [20] did not choose especially lean patients for their study. BMI was not an exclusion crite-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unluhizarci et al [20] did not choose especially lean patients for their study. BMI was not an exclusion crite-…”
Section: Discussionmentioning
confidence: 99%
“…Unluhizarci et al [20] showed that IH is associated with some degree of insulin resistance and increased tendency for glucose intolerance notably in obese women with IH.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown an increased prevalence of glucose intolerance in women with idiopathic hirsutism, who actually have normal serum androgen levels (12). From another point of view it has been shown that hyperinsulinemia during OGTT might activate the androgen pathway of the adrenal cortex (18).…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, a number of androgen excess disorders are diagnosed by exclusion such as PCOS. Although hirsutism is the most common feature of androgen excess, it is well known that not all patients with hirsutism have overt androgen excess as in idiopathic hirsutism (12,13). We have previously shown that a number of patients with hirsutism had hyperandrogenemia with normal ovaries and regular cycles.…”
Section: Discussionmentioning
confidence: 89%
“…No entanto, é extremamente laborioso e caro, sendo inexequível da prática, na maioria dos serviços (6). Por isso, tem-se aferido a sensibilidade insulínica através de métodos mais simples, como o teste oral de tolerância à glicose com a dosagem de insulina (TOTG), o cálcu-lo da relação glicose/insulina (G/I), a insulinemia de jejum ou basal (IB) e pós-prandial, além do homeostatic model assessment (HOMA) (4,(7)(8)(9).…”
unclassified